Abuse of Authority in Tax Collection Through the Application of Tax Seizure (Gijzeling) by the Directorate General of Taxes - Seselia Ongso; Evi Kongres (Ridwan Institute, 2026)
This study discusses the authority of the Directorate General of Taxes (Direktorat Jenderal Pajak, Dirjen Pajak) in the process of tax collection through the application of tax hostage taking (gijzeling) and the legal consequences of its application if it is carried out based on tax collection that contains deviations of authority. The formulation of this research problem includes: how is the authority of the Director General of Taxes in the tax collection process through the application of gijzeling, and what are the legal consequences of the implementation of gijzeling carried out through tax collection which contains deviations of authority, in terms of legal certainty and legal protection of taxpayers. This study uses normative-empirical legal research methods with legislative, conceptual, and case study approaches. The results of the study show that the authority of the Director General of Taxes in implementing gijzeling is attribution authority given by laws and regulations as a tax collection instrument that can only be used after all material and procedural requirements determined by law are met. This condition results in legal uncertainty, reduced legal protection for taxpayers, and opens up the possibility of legal liability for government actions carried out illegally. This study concludes that the effectiveness of tax collection through gijzeling must be balanced with compliance with the principles of legality, proportionality, and accountability so that the implementation of tax authority does not develop into a form of abuse of authority that is detrimental to taxpayers.